(untitled) (Medical Forum Monthly, 2024)
Objective: The objective of this study is to determine the trend of poisoning in Muzaffarabad AJK. Study Design: Retrospective study. Place and Duration of Study: This study was conducted at combined Military Hospital (CMH) Muzaffarabad (AJK) during the period of 1st January 2009 to 31st December 2010. Material& Methods: One hundred & forty cases of poisoning was brought in hospital. Information regarding Age, Gender, demography, manner, time of occurrence, and patient outcome was confirmed from hospital records and collected data was analyzed. Results: There were 98 female and 42 mate victims involved in this study and maximum cases belong to second and third decade of life (23.57% and 48.57% respectively. Most common manner of poisoning was suicidal / attempts. Most incidences of poisoning occur in month of June and an organophosphorous compounds was leading cause of poisoning followed by Benzodiazepines. Conclusion: Organophosphorous compounds are the major chemical agents which pose a health threat particularly to young people.